2017
DOI: 10.1038/s41598-017-02187-0
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of shear wave elastography for the diagnosis of prostate cancer: A meta-analysis

Abstract: Many studies have established the high diagnostic accuracy of shear wave elastography (SWE) for the detection of prostate cancer (PCa); however, its utility remains a subject of debate. This meta-analysis sought to appraise the overall accuracy of SWE for the detection of PCa. A literature search of the PubMed, Embase, Cochrane Library, Web of Science and CNKI (China National Knowledge Infrastructure) databases was conducted. In all of the included studies, the diagnostic accuracy of SWE was compared with that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 53 publications
1
40
0
Order By: Relevance
“…9,10 Shear wave elastography (SWE) is another diagnostic technique that can assess prostate stiffness, which is higher in PCa than benign tissue. [11][12][13][14] However, we did not find a published report comparing multiparametric TRUS, including grayscale imaging, color Doppler imaging, CEUS, and SWE, with multiparametric MRI in the diagnosis of PCa during our literature review.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…9,10 Shear wave elastography (SWE) is another diagnostic technique that can assess prostate stiffness, which is higher in PCa than benign tissue. [11][12][13][14] However, we did not find a published report comparing multiparametric TRUS, including grayscale imaging, color Doppler imaging, CEUS, and SWE, with multiparametric MRI in the diagnosis of PCa during our literature review.…”
mentioning
confidence: 81%
“…All patients maintained a left-lateral lie position with bent knees. Conventional ultrasound (US) examinations were performed with an Aixplorer US system (SuperSonic Imagine, Aix-en-Provence, France) using an SE12-3 transrectal end-fire probe (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Grayscale and color Doppler imaging was performed by measuring 3 diameters of the prostate to observe the suspicious lesions ( Figures 1 and 2).…”
Section: Multiparametric Trus Conventional Grayscale and Color Dopplementioning
confidence: 99%
“…Sang et al [35] and Woo et al [36] found that SWE showed an excellent PCa detection rate. The lack of consensus regarding the stiffness cut-off values differentiating the malignant and benign tissues made it difficult to standardize SWE guided biopsy.…”
Section: The Effectiveness Of Elastography Based On Available Researchmentioning
confidence: 99%
“…In the past decade, six meta-analyses discussing the application of elastography as a tool for a prostate cancer imaging were published (Table I) [23,[33][34][35][36][37]. In all available studies, TRES showed superiority in PCa detection in comparison to standard TRUS.…”
Section: The Effectiveness Of Elastography Based On Available Researchmentioning
confidence: 99%
“…This type of elastography has the advantage of providing quantitative information regarding the tissue stiffness and deformation, with no difference in the intra-observer reproducibility [39]. The two studies published so far that compared SWE with sextant prostate biopsy demonstrated high sensitivity and specificity for the diagnosis of PCa (96% and 95% in the first study 90% and 80% in the second study) [40,41].…”
Section: New Ultrasound Techniquesmentioning
confidence: 99%